Promising Anticancer Stand-ins of Phyllanthus Species - Simran; Vani; Kriplani, Priyanka; Guarve, Kumar (Current Indian Science, 2023)
BackgroundPhyllanthus species plants along with their active constituent phyllanthin, are the most widely used plants to cure various diseases. Present studies indicate their applicability as anti-diabetic, anti-malarial, antiplasmodial, anti-viral, anti-inflammatory, antibacterial, antioxidant, antineoplastic, diuretic, nephroprotective, hypolipidemic, and hepatoprotective properties.ObjectiveThe objective of the present review is to study the recent literature and patents, including the various methods of extraction and isolation of phyllanthin along with its pharmacokinetics and clinical trials and mainly focussing on their anticancer potential along with a brief on other pharmacological activities.MethodsRecent prose and patents focussing on the anticancer potential of mainly P. amarus and P. niruri have been highlighted with special emphasis on scientific novelty and impact.ResultsBoth P.amarus and P.niruri displayed good anticancer potential in multiple tumors and synergistic effects when combined with other anticancer drugs. Ne isolation/extraction methods, clinical trials, and pharmacokinetic studies have been discussed.ConclusionThe anticancer potential of P.amarus and P.niruri has opened new avenues for further research. Clinical trials are the need of the hour to validate and confirm the tumor-suppressing properties of both plants.
Keywords: P. amarus